1996
DOI: 10.1042/bj3190131
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic activity of the endoplasmic reticulum-resident protein microsomal epoxide hydrolase towards carcinogens is retained on inversion of its membrane topology

Abstract: Diol epoxides formed by the sequential action of cytochrome P-450 and the microsomal epoxide hydrolase (mEH) in the endoplasmic reticulum (ER) represent an important class of ultimate carcinogenic metabolites of polycyclic aromatic hydrocarbons. The role of the membrane orientation of cytochrome P-450 and mEH relative to each other in this catalytic cascade is not known. Cytochrome P-450 is known to have a type I topology. According to the algorithm of Hartman, Rapoport and Lodish [(1989) Proc. Natl. Acad. Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…4, lane 3). These glycosylation results are qualitatively similar to those previously reported for mEH when the potential glycosylation site was inserted at position 39 or 303 (20). These studies, however, analyzed only total expressed protein with an indicated lower limit of detec- …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…4, lane 3). These glycosylation results are qualitatively similar to those previously reported for mEH when the potential glycosylation site was inserted at position 39 or 303 (20). These studies, however, analyzed only total expressed protein with an indicated lower limit of detec- …”
Section: Discussionsupporting
confidence: 77%
“…These results are supported by previous studies on cytochrome P450 IIE1 (52) and P450 1A1 (53). Because mEH residues 39, 303 (20), and 432 (this study) are expressed on the same side of the membrane in either the type I or type II orientation, based on glycosylation site analysis, a model with three transmembrane domains would be consistent with the current available data. The oligomerization of mEH could then lead to a system spanning the membrane multiple times, which would be consistent with its role as a bile acid transporter.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, mEH, like the majority of CYPs, is an endoplasmic reticulum (ER)-resident protein. With respect to their membrane topology, CYP and mEH are type-I proteins (Black 1992 ; Friedberg et al 1996 ). Their short N-termini that precede their single transmembrane helix face the ER lumen while their catalytic domains are sitting on the cytoplasmatic surface of the ER.…”
Section: Introductionmentioning
confidence: 99%